2010
DOI: 10.1007/s10509-009-0253-x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the photogravitational restricted three-body problem with variable masses

Abstract: This paper investigates the stability of equilibrium points in the restricted three-body problem, in which the masses of the luminous primaries vary isotropically in accordance with the unified Meshcherskii law, and their motion takes place within the framework of the GyldenMeshcherskii problem. For the autonomized system, it is found that collinear and coplanar points are unstable, while the triangular points are conditionally stable. It is also observed that, in the triangular case, the presence of a constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 10 publications
2
42
0
Order By: Relevance
“…Equation (14) is quadratic in λ and has the roots: (17) and Hence, the eccentricity of the long and short period orbit is found respectively by substituting the respective equations of (17) in (16) …”
Section: Now the Corresponding Characteristics Equation Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…Equation (14) is quadratic in λ and has the roots: (17) and Hence, the eccentricity of the long and short period orbit is found respectively by substituting the respective equations of (17) in (16) …”
Section: Now the Corresponding Characteristics Equation Of Thementioning
confidence: 99%
“…Studies of this kind include among many, Radzievskii [8], Simmons et al [13], Singh and Leke [17]. Further generalizations are the case when the shapes of the participating bodies are not perfect spheres.…”
Section: Introductionmentioning
confidence: 99%
“…Shrivastava et al in [46] evaluated the equilibrium points in the Robes restricted problem of three-bodies with effect of perturbations in the coriolis and centrifugal forces. Singh et al in [50][51][52][53][54][55][56][57][58][59] studied the restricted problem of three-bodies and four-bodies in circular and elliptic cases with different perturbations. Khanna et al in [29,30] explored the existence and stability of libration points in the restricted three-body problem when the smaller primary is a triaxial rigid body and the bigger one an oblate spheroid and observed that there are five libration points in which three collinear libration points are unstable and two triangular points are stable for the particular mass parameter.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the collinear points are unstable and the triangular points are conditionally stable depending on the radiation factor and oblateness. Singh [11] investigated the stability of equilibrium points in the restricted three body problem in which the masses of the luminous primaries vary isotropically in accordance with the unified Meshcherskii law. They found that the collinear points are unstable and the triangular points are conditionally stable in the autonomized system.…”
Section: Introductionmentioning
confidence: 99%